Rediscovery of Cerceris fumipennis (Hymenoptera: Crabronidae) in British Columbia, Canada, with notes on geographic variation and nesting habits. Issue 4 (9th October 2014) - Kimoto, Troy; Buck, Matthias
Abstract: Within Canada, Cerceris fumipennis Say (Hymenoptera: Crabronidae) is known to occur in Ontario and Québec but there is also one historic record from 1935 of two female specimens captured in Lytton, British Columbia. No other records have been recorded for the last 77 years. In 2012 and 2013, one male and four females were captured in a sweep net adjacent to a gravel parking lot in Merritt, British Columbia. Although there are differences in size and colouration between the British Columbia and eastern species, the variation between the populations does not warrant assigning a new name to this geographical race. Résumé: Au Canada, Cerceris fumipennis Say (Hymenoptera: Crabronidae) est connu pour être présent en Ontario et au Québec, mais un relevé historique datant de 1935 rapporte deux femelles capturées à Lytton, Colombie-Britannique. Aucun autre relevé n'a été enregistré au cours des 77 dernières années. En 2012 et 2013, un mâle et quatre femelles ont été capturés dans un filet fauchoir adjacent à un stationnement en gravier à Merritt, Colombie-Britannique. Même s'il y a des différences au niveau de la taille et de la coloration entre les espèces de la Colombie-Britannique et celles de l'est, la variation entre les populations ne justifie pas l'attribution d'un nouveau nom à cette race géographique.